Traumatic Brain Injury Rehabilitation in Hong Kong: A Review of Practice and Research - Junhong Yu; Helena M. K. Tam; Tatia M. C. Lee (Behavioural Neurology)
Background. The rising public health concern regarding traumatic brain injury (TBI) implies a growing need for rehabilitation services for patients surviving TBI. Methods. To this end, this paper reviews the practices and research on TBI rehabilitation in Hong Kong so as to inform future developments in this area. This paper begins by introducing the general situation of TBI patients in Hong Kong and the need for rehabilitation. Next, the trauma system in Hong Kong is introduced. Following that is a detailed description of the rehabilitation services for TBI patients in Hong Kong, as exemplified by a rehabilitation hospital in Hong Kong. This paper will also review intervention studies on rehabilitating brain-injured populations in Hong Kong with respect to various rehabilitation goals. Lastly, the implications of culture-related issues will be discussed in relation to TBI. Results/Conclusions. The intervention studies conducted in Hong Kong are generally successful in achieving various rehabilitative outcomes. Additionally, certain cultural-related issues, such as the stigma associated with TBI, may impede the rehabilitative process and lead to various psychosocial problems.